2008
DOI: 10.1021/jp808360y
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure of Disordered Conjugated Polymers: Polythiophenes

Abstract: Electronic structure of disordered semiconducting conjugated polymers was studied. Atomic structure was found from a classical molecular dynamics simulation and the charge patching method was used to calculate the electronic structure with the accuracy similar to the one of density functional theory in local density approximation. The total density of states, the local density of states at different points in the system and the wavefunctions of several states around the gap were calculated in the case of poly(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
127
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(134 citation statements)
references
References 43 publications
6
127
1
Order By: Relevance
“…it is increased (decreased) if the acceptance rate is higher (lower) than 25%. The optimization is deemed to be converged and is terminated when the change in the objective function is lower than a threshold, here set to 10 10  kcal/mol/Å. For all studied systems, the optimized objective function is always very similar if the procedure is repeated with a different random seed, indicating that there is a single minimum or a number of equivalent minima.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…it is increased (decreased) if the acceptance rate is higher (lower) than 25%. The optimization is deemed to be converged and is terminated when the change in the objective function is lower than a threshold, here set to 10 10  kcal/mol/Å. For all studied systems, the optimized objective function is always very similar if the procedure is repeated with a different random seed, indicating that there is a single minimum or a number of equivalent minima.…”
Section: Methodsmentioning
confidence: 99%
“…Large-scale electronic structure calculations are then used to correlate the local structure with the observable electronic structure properties. 6,10 Another new class of applications of classical MD is the elucidation of experiments in ultrafast electronic spectroscopy of biomolecules. It was recently shown that long quantum coherences can be observed in biological molecules [11][12][13] and the aim of atomistic simulations is to explain how the (classical) environment can influence the (quantum) evolution of the electronic states.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that many studies predict a more broad density-of-states for the chromophores than is expected experimentally [80,[107][108][109][110]. Therefore, some studies have successfully utilized Koopman's approximation, which effectively maps the density-of-states to a single narrow peak by assuming that each chromophore is identical with ∆E ij = 0 [104,111,112].…”
Section: Charge Mobilitymentioning
confidence: 99%
“…Calculations of long polymer chains in conformations obtained from molecular dynamics simulations suggest that the main cause of localization of the orbital in single polymer chains is the variation (disorder) in the dihedral angles of the conjugated backbone, in the 15°-35° range for different polymers, which causes a variation of the electronic coupling between monomers corresponding to 5-20% of the average coupling. [12][13][14] Therefore, we start considering a purely electronic disordered Hamiltonian (the effect of electronphonon coupling will be discussed later) with one state i per site i (representing a monomer) and nearest neighbor coupling: consider only the disorder in the off-diagonal terms, following the indications from our atomistic studies [13]  contain states in two separate energy regions. The wavefunctions in the low energy band have their probability density concentrated on the sites corresponding to the low energy monomer and viceversa.…”
mentioning
confidence: 99%